Back Cover: Carboranylphosphinic Acids: A New Class of Purely Inorganic Ligands (Chem. Eur. J. 11/2016). Issue 11 (25th January 2016) - Oleshkevich, Elena; Teixidor, Francesc; Choquesillo‐Lazarte, Duane; Sillanpää, Reijo; Viñas, Clara
Abstract : In the arylphosphinate compounds the carbon atom linked to the phosphorus is part of an organic functional group like a phenyl moiety. Conversely, in a carboranylphosphinate the carbon atom linked to the phosphorus is part of an icosahedron. The phenyl ring is aromatic, as it is the carboranyl cluster. However, the latter is tridimensional whereas the phenyl ring is planar. The image represents the symbolic projection on the plane of this tridimensional molecule. In this process of tri‐ to bidimensionality, many chemical and physical properties are modified. This is also shown in the image through the modification of the optical properties of the two distinct phosphinates. More information can be found in the Communication by C. Viñas et al.page 3665 ff.